Review of surface metrology artifacts for additive manufacturing - Mietliński, Patryk; Gapiński, Bartosz; Królczyk, Jolanta B.; Niesłony, Piotr; Bogdan-Chudy, Marta; Trych-Wildner, Anna; Wojciechowska, Natalia; Królczyk, Grzegorz M.; Wieczorowski, Michał; Bartkowiak, Tomasz (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
Test artifacts, resembling real machine parts, allow for quantitative evaluation of system performance and provide insight into individual errors, aiding in improvement and standardization of additive manufacturing. The article provides a comprehensive overview of existing test artifacts, categorized based on geometric features and the material used. Various measurement techniques such as stylus profilometry and computed tomography are employed to assess these artifacts. It is also shown that the selective laser melting (SLM) technology and titanium alloys are prevalent in artifact creation. Specific artifact categories include slits, angular aspects, length parameters, variable surfaces, and others, each accompanied by examples from research literature, highlighting diverse artifact designs and their intended applications. The paper critically discusses the main problems with existing geometries. It underscores the importance of user-friendly and unambiguous artifacts for dimensional control, particularly in surface metrology. Furthermore, it anticipates the continued growth of metrological verification in future manufacturing environments, emphasizing the need for precise and reliable measurement results to support decision-making under production conditions.